2013
DOI: 10.1161/circulationaha.113.002598
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Coronary Artery Calcium Score in Combination With Conventional Cardiovascular Risk Factors

Abstract: Background The coronary artery calcium (CAC) score predicts coronary heart disease (CHD) events, but methods for interpreting the score in combination with conventional CHD risk factors have not been established. Methods and Results We analyzed CAC scores and CHD risk factor measurements from 6757 Black, Chinese, Hispanic and white men and women aged 45–84 years in the Multi-Ethnic Study of Atherosclerosis (MESA). CAC was associated with age, sex, race-ethnicity, and all conventional CHD risk factors. Multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 34 publications
2
49
0
Order By: Relevance
“…Furthermore, baPWV improved the ability of traditional risk factors (measured using standardized procedures and validated questionnaires) for detecting prevalent CAC. This information may help decide when to order a CAC scan, and aid in the interpretation of the score [23].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, baPWV improved the ability of traditional risk factors (measured using standardized procedures and validated questionnaires) for detecting prevalent CAC. This information may help decide when to order a CAC scan, and aid in the interpretation of the score [23].…”
Section: Discussionmentioning
confidence: 99%
“…may provide supplementary prognostic information'' compared to CAC. In keeping with this, it has been proposed that ECC may be used as a marker of systemic, noncoronary atherosclerosis (45). Among participants of the MESA study, ECC load has been shown to correlate with insulin resistance (46).…”
Section: Discussionmentioning
confidence: 97%
“…29 Because vascular calcification is independently associated with hypertension in epidemiological studies and RANKL is essential for calcification, it is important to understand that RANKL is an activator of the renin-angiotensin system. 7,30 However, infusion of angiotensin II (100 ng/kg per minute) in ovariectomized ApoE −/− mice significantly increased the expression of RANKL and calcification in vivo, whereas administration of angiotensin II receptor blocker (olmesartan, 3 mg/kg per day) decreased the calcification and expression of bone markers, 30 which introduce a molecular feedback between endocrinology pathways and vascular calcification in the pathogenesis of hypertension. Cross-talk between the renin-angiotensin II and RANKL system has been suggested to work in a vicious cycle to promote vascular calcification in atherosclerosis.…”
Section: Mechanisms Of Intimal Calcification (Atherosclerosis)mentioning
confidence: 99%
“…Agatston et al 6 devised a coronary artery calcification (CAC) scoring scheme, and others have shown calcium score to be a better predictor of future events than the Framingham risk index alone. 7 There is also a close relationship between the presence of CAC and atherosclerotic plaque burden, with angiographic studies showing high sensitivity but poor specificity of CAC score for predicting obstructive disease. 8 Physical activity is known to decrease cardiovascular mortality; however, there is no relationship between the extent of coronary calcification as assessed by CT in individuals engaged in moderate exercise.…”
mentioning
confidence: 99%